Macrolide Antibiotics and the Risk of Cardiac Arrhythmias - Albert, Richard K.; Schuller, Joseph L. (American journal of respiratory and critical care medicine, 2014)
Randomized, controlled trials have demonstrated that chronic therapy with macrolide antibiotics reduces the morbidity of patients with cystic fibrosis, non-cystic fibrosis bronchiectasis, chronic obstructive pulmonary disease, and nontuberculous mycobacterial infections. Lower levels of evidence indicate that chronic macrolides are also effective in treating patients with panbronchiolitis, bronchiolitis obliterans, and rejection after lung transplant. Macrolides are known to cause torsade des pointes and other ventricular arrhythmias, and a recent observational study prompted the FDA to strengthen the Warnings and Precautions section of azithromycin drug labels. This summary describes the electrophysiological effects of macrolides, reviews literature indicating that the large majority of subjects experiencing cardiac arrhythmias from macrolides have coexisting risk factors and that the incidence of arrhythmias in absence of coexisting risk factors is very low, examines recently published studies describing the relative risk of arrhythmias from macrolides, and concludes that this risk has been overestimated and suggests an approach to patient evaluation that should reduce the relative risk and the incidence of arrhythmias to the point that chronic macrolides can be used safely in the majority of subjects for whom they are recommended.